A one-pot synthesis of 7,11-diaryl-2,4-diazaspiro[5,5]undecane-3-oxo (or thioxo)-1,5,9-triones - Ahmed, M Giasuddin; Ahmed, Syeda Asghari; Romman, UKR; Akhter, Kawsari; Halim, Md Ershad; Naher, Shamsun; Aslam, Md; Ahmed, S Mosaddeq (Journal of the Bangladesh Chemical Society, 2012)
Spiro compounds 7,11-diaryl-2,4-diazaspiro[5,5]undecane-1,3,5,9-tetraones 3a-d were prepared by carrying out reactions between diarylideneacetones, (ArCH=CH)2C=O, 2a-d [Ar= 2-CH3C6H4, 4-CH3C6H4, 4-(CH3)2NC6H4 and 4-HOC6H4 respectively] and barbituric acid (1a) under refluxing condition in aqueous ethanol medium without using any catalyst. Under similar conditions the corresponding 7,11-diaryl-3-thioxo-2,4-diazaspiro[5,5]undecane-1,5,9-triones 3e-g were synthesized from the reactions of diarylideneacetones 2a, 2d and 2e [Ar= 4-ClC6H4] with 2-thiobarbituric acid (1b). The structures of the spiro compounds were established with the help of their UV, IR, 1H NMR, 13C NMR and mass spectral data and elemental analyses. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9702 Journal of Bangladesh Chemical Society, Vol. 24(2), 135-142, 2011